2017
DOI: 10.1016/j.lithos.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Continental origin of the Gubaoquan eclogite and implications for evolution of the Beishan Orogen, Central Asian Orogenic Belt, NW China

Abstract: The Gubaoquan eclogite occurs in the Paleozoic Beishan Orogen of NW China. Previously it has been interpreted as a fragment of subducted oceanic crust that was emplaced as a mélange within continental rocks. Contrary to this, we demonstrate that the Gubaoquan eclogite protolith was a Neoproterozoic basic dyke/sill which intruded into Proterozoic continental rocks. The SHRIMP U-Pb zircon dating of the metamorphic rims of the Gubaoquan eclogite yields an age 466 ± 27 Ma. Subdued heavy rare earth element abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 104 publications
(174 reference statements)
2
33
0
Order By: Relevance
“…Combined with all the data presented by previous studies, in this study, we present that the Liuyuan Basin is a back-arc basin and that the pillow lavas and its associated rocks such as clastic sediments and limestones formed in a back-arc basin tectonic setting. The following reasons are demonstrated: First, according to the previous geological mapping and combined with geochronology data collected in this paper ( Figure 3 and Table Third, eclogites discovered in the Gubaoquan area have a metamorphic age of 465-467 Ma Qu et al, 2011;Saktura et al, 2017) and with a formation age of 920 Ma (Saktura et al, 2017). In the south of the Liuyuan Basin, although large areas of land were covered by the Quaternary sediments, eclogite was still found in the Hongliuxia area~100 km south of our study area by Wang et al (2016), and it has a metamorphic age of 411 Ma and formation age of 1316 Ma.…”
Section: Back-arc Basin or Oceanic Basin?mentioning
confidence: 78%
See 1 more Smart Citation
“…Combined with all the data presented by previous studies, in this study, we present that the Liuyuan Basin is a back-arc basin and that the pillow lavas and its associated rocks such as clastic sediments and limestones formed in a back-arc basin tectonic setting. The following reasons are demonstrated: First, according to the previous geological mapping and combined with geochronology data collected in this paper ( Figure 3 and Table Third, eclogites discovered in the Gubaoquan area have a metamorphic age of 465-467 Ma Qu et al, 2011;Saktura et al, 2017) and with a formation age of 920 Ma (Saktura et al, 2017). In the south of the Liuyuan Basin, although large areas of land were covered by the Quaternary sediments, eclogite was still found in the Hongliuxia area~100 km south of our study area by Wang et al (2016), and it has a metamorphic age of 411 Ma and formation age of 1316 Ma.…”
Section: Back-arc Basin or Oceanic Basin?mentioning
confidence: 78%
“…Third, eclogites discovered in the Gubaoquan area have a metamorphic age of 465–467 Ma (Liu et al, 2011; Qu et al, ; Saktura et al, ) and with a formation age of 920 Ma (Saktura et al, ). In the south of the Liuyuan Basin, although large areas of land were covered by the Quaternary sediments, eclogite was still found in the Hongliuxia area ~100 km south of our study area by Wang et al (), and it has a metamorphic age of 411 Ma and formation age of 1316 Ma.…”
Section: Discussionmentioning
confidence: 99%
“…1 – Hongshishan mélange, 2 – Xingxingxia‐Shibanjing mélange, 3 – Hongliuhe‐Xichangjing mélange, 4 – Liuyuan mélange. Data: 1 – Yuan et al (2015); 2 – Mei et al (1999); Ye et al (2013); Liu et al (2015); Yuan et al (2015); Saktura et al (2017); Soldner et al (2020); 3 – Jiang, He, Zong, Zhang, and Zhao (2013); 4 – He, Sun, Mao, Zhong, and Zhang (2015); Yuan et al (2019); 5 – Ao et al (2016); 6 – Niu et al (2019) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that an extensive Precambrian basement, referred to as the Beishan complex, occurs in the arc terranes of the Beishan orogenic belt, except for the Quershan Terrane (Figure 1b; BGMRGP, 1996; He et al, 2005; Yang et al, 2012; Zuo et al, 1991), but their protolith ages of many so‐called Precambrian rocks are speculative. Although Precambrian ages have been obtained from some rocks by the zircon U–Pb dating (He et al, 2015; Jiang et al, 2013; Liu et al, 2015; Niu et al, 2019; Saktura et al, 2017; Soldner et al, 2020; Ye et al, 2013; Yuan et al, 2015, 2019), many of the rocks previous thought to be Precambrian are actually Palaeozoic in age (Song et al, 2015, 2016; Song, Xiao, Han, Li, et al 2013; Song, Xiao, Han, & Tian, 2013, Song, Xiao, Han, Tian, & Wang, 2013 Zheng, Li, Xiao, & Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation